2016
DOI: 10.1080/13506129.2016.1207626
|View full text |Cite
|
Sign up to set email alerts
|

Incidence rate of amyloidosis in patients from a medical care program in Buenos Aires, Argentina: a prospective cohort

Abstract: This is the first paper to report the incidence density of ATTRwt, AL and AA amyloidosis in Latin America. Our results are consistent with other studies from other regions. Although systemic amyloidosis is a rare disease, it is a major health problem because of its morbi-mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
14
0
4
Order By: Relevance
“…These light chains form oligomers and bind to cellular and extracellular matrix proteins causing direct toxicity and amyloid deposition in organs such as the heart and kidneys 1,2 . Studies are limited regarding the annual incidence of AL, but estimates range from 3 to 13 cases per million person-years [2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…These light chains form oligomers and bind to cellular and extracellular matrix proteins causing direct toxicity and amyloid deposition in organs such as the heart and kidneys 1,2 . Studies are limited regarding the annual incidence of AL, but estimates range from 3 to 13 cases per million person-years [2][3][4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…One epidemiologic study reported incidence densities of 6.13 per million person-years for AL amyloidosis and 1.21 per million person-years for AA amyloidosis. 7 Depending on the type of amyloidosis, GI tract involvement varies. The GI tract is affected in approximately 60% of patients with AA amyloidosis, but less common in patients with AL amyloidosis, with only 8% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of organ involvement was studied: cardiac involvement (development of congestive heart failure, arrhythmia attributable to amyloidosis, or biopsy positive for amyloidosis, imaging involvement (cardiac MRI with gadolinium, echocardiogram with strain)); neurological involvement (polyneuropathy, autonomic dysfunction attributable to amyloidosis or biopsy positive for amyloidosis); nephrologic involvement (kidney failure, nephrotic syndrome, urine protein attributable to amyloidosis, or biopsy positive for amyloidosis); and involvement of other organs attributable to amyloidosis or biopsy positive for amyloidosis (Aguirre et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%